Creditor Protection and Credit Volatility - Arturo Galindo; Alejandro Micco (Inter-American Development Bank, Research Department, 2005)
This paper studies the relationship between creditor protection and credit volatility. During the negative phase of the business cycle, credit contracts more in countries with poor creditor protection. For similar shocks to business conditions, credit is more volatile in countries where creditors are de facto weakly protected. We test this idea using a dataset on legal determinants of finance in a panel of data of aggregate credit growth for a sample of 139 countries during the period 1990-2003. We find support for the view that better legal protections significantly reduce the impact of exogenous shocks on credit. The results are statistically and economically significant and robust to alternative measures of creditor protection, the inclusion of variables that reflect different stages of economic development and the restriction of our sample to only developing countries.
Keywords: 330; Gläubigerschutz; Kredit; Volatilität; Schätzung; Welt